1997
DOI: 10.1103/physreve.56.245
|View full text |Cite
|
Sign up to set email alerts
|

Power-law sensitivity to initial conditions within a logisticlike family of maps: Fractality and nonextensivity

Abstract: Power-law sensitivity to initial conditions, characterizing the behaviour of dynamical systems at their critical points (where the standard Liapunov exponent vanishes), is studied in connection with the family of nonlinear 1D logistic-like maps xt+1 = 1 − a |xt| z , (z > 1; 0 < a ≤ 2; t = 0, 1, 2, . . .).The main ingredient of our approach is the generalized deviation law lim ∆x(0)→01−q (equal to e λ 1 t for q = 1, and proportional, for large t, to t 1 1−q for q = 1; q ∈ R is the entropic index appearing in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
158
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(169 citation statements)
references
References 35 publications
10
158
0
1
Order By: Relevance
“…The value of q which allows for a linear growth of S q (t), obtained through this procedure, happens to coincide with the value q * obtained in a completely different method by studying the power-law sensitivity to initial conditions [14]. There exists also another method, based only on the geometrical description of the multifractal attractor existing at a c , which gives exactly the same value of q [14].…”
Section: B the Edge Of Chaosmentioning
confidence: 96%
See 3 more Smart Citations
“…The value of q which allows for a linear growth of S q (t), obtained through this procedure, happens to coincide with the value q * obtained in a completely different method by studying the power-law sensitivity to initial conditions [14]. There exists also another method, based only on the geometrical description of the multifractal attractor existing at a c , which gives exactly the same value of q [14].…”
Section: B the Edge Of Chaosmentioning
confidence: 96%
“…In particular it has been shown that such an entropy covers some types of anomalies due to a possible multifractal structure of the relevant phase space. For example, whenever we have long-range interactions [19], long-range microscopic memory [20], or multifractal boundary conditions [14]. We discuss in the rest of the paper the following results obtained for the logistic map [8]:…”
Section: The Logistic Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…After these works on the logistic map, numerical evidences supporting this framework came also from the studies of other low-dimensional dynamical systems, such as the z-logistic map family [6,7], the Henon map [8] and the asymmetric logistic map family [9]. Besides these numerical investigations, analytical treatment of the subject is also available recently in a series of paper by Baldovin and Robledo [10].…”
Section: Introductionmentioning
confidence: 98%